The acute leukocyte and cytokine response of older adults to resistance exercise in normobaric hypoxia - Allsopp, Giselle; Addinsall, Alex; Stephenson, Garth; Basheer, Faiza; Della Gatta, Paul; Hoffmann, Samantha; Russell, Aaron; Wright, Craig (Biology of Sport, 2023)
Ageing causes a decline in leukocyte function and blunted leukocyte responses to resistance exercise. Systemic hypoxia exposure augments the leukocyte response to resistance exercise in young adults, yet this response remains uncharacterised in older adults. This study characterised the effects of normobaric hypoxia on the acute leukocyte and inflammatory cytokine responses to resistance exercise in older adults. We recruited 20 adults aged 60–70 years to perform an acute bout of resistance exercise in normobaric hypoxia (FiO₂ 14.4%; n = 10) or normoxia (FiO₂ 20.93%; n = 10). Participants completed 4×10 repetitions of lower and upper body exercises at 70% of their predicted 1-repetition maximum. Venous blood was sampled before and up to 24 hours post-exercise to quantify neutrophils, lymphocytes, monocytes, eosinophils, basophils and cytokines (IL-1β, IL-4, IL-6, IL-8, IL-10, TNFα). Flow cytometry was used to classify lymphocytes as T (CD4+ helper and CD8+ cytotoxic), B and NK cells, in addition to the expression of the senescence marker CD45RA on T cells. The hypoxic group showed a larger lymphocyte response over the 24 hours post-exercise compared to the normoxic group (p = 0.035). Specifically, there were greater concentrations of CD4+ T helper cells following hypoxic exercise compared to normoxia (p = 0.046). There was also a greater proportion of CD45RA+ CD4+ T helper cells, suggesting that the cells were more senescent (p = 0.044). Hypoxia did not impact any other leukocyte population orcytokine following exercise. Normobaric hypoxia increasesthe lymphocyte response to an acute bout of resistance exercise in older adults.